The big carve-up - Anonymous (The Economist, 2021)
[...]taxing rights are allocated first to wherever profits are produced (the "source") and then to wherever the parent company is headquartered (or "resident"). [...]tax competition has encouraged companies to shuffle their reported profits to low-tax places. [...]any deal will involve compromises.
Num Pages: 69-70 Section: Finance & economics